Knowledge and attitude about early childhood caries among pregnant mothers from low socioeconomic status: A questionnaire study - Pooja Rajan; Ramesh Krishnan; Suresh Kumar; Suraj Nair (Wolters Kluwer Medknow Publications, 2017)
Background: For health and well-being, oral health is an integral component. Unfortunately, many children are afflicted with dental caries at an early age, even those as young as 12 months. By imparting knowledge, awareness among parents about this disease can bring about reduction of early childhood caries (ECC) at an early stage. Aim: The aim of this study was to evaluate knowledge and attitude of expectant mothers about ECC and to reassess the level of knowledge after giving anticipatory guidance. Materials and Methods: The questionnaire consisted of 10 questions which were distributed to 100 participants after which anticipatory guidance was given to them. After 15 days, the same questionnaire was distributed among the participants with order of the questions interchanged. Chi-square test was used for statistical analysis. Results: There was a significant improvement in the knowledge and attitude about the disease after giving the anticipatory guidance among the participants. P < 0.01 and the result were statistically significant. Conclusion: Knowledge and attitude of mothers were found to increase on provision of anticipatory guidance, which was retained even after 15 days.